IMPLIKASI KONSEP MODERASI BERAGAMA TERHADAP MULTIKULTURALISME DI INDONESIA - Febrianto, Sobri; Munfarida, Elya (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2023)
This research is a research that discusses religious moderation and its implications for multiculturalism in Indonesia. Today the term religious moderation is increasingly being hoisted by the government as a concept that becomes a middle way and solution to pluralism in multicultural Indonesian society. This concept was initiated by the Ministry of Religious Affairs and was massively raised in the era of Minister of Religious Affairs Lukman Hakim Saifuddin. This research is positioned to try to dissect whether the concept of religious moderation has a good impact on multiculturalism in Indonesia. Where this research borrows a theory from John Rawls related to Multicultural Philosophy which is in line with the life of multicultural society in Indonesia. This research uses qualitative methods and library research type. There are several results found including, John Rawls' basic theory related to the philosophy of Multiculturalism actually arises from justice and mlticultural side by side with culture or culture. So from the clash of the meeting of these three variables, Rawls conceptualized at least several points that became the basis of Multicultural society, namely Justice as Fairnes, Veil of Ignorance, Maximum Rules, Reflective Equilibrium, and Principal of Liberty / Principal of Equal Liberty and Difference Principle. Meanwhile, in the concept of religious moderation in Indonesia, it has several indicators that indicate a society uses religious moderation or not. Some of these indicators are National Commitment, Tolerance, Anti-Violence, and Accommodating to Local Culture. Conceptually and theoretically it says that the concept of religious moderation has implications for multicultural society represented in John Rawls' philosophical theory of multiculturalism, but in practice it has not had a major impact due to several factors such as the large faktr of the Indonesian state and the uneven understanding of religious moderation for people in Indonesia.